Entering an emotional minefield: professionals' experiences with facilitators to address abuse in child interviews - Ane Ugland Albaek; Per-Einar Binder; Anne Marita Milde (BMC, 2019)
Abstract Background Extensive research documents that child abuse is widespread and that it has detrimental effects on victims' physical, psychological and social well-being. Efforts to help abused children by removing stressors and administering restorative care can reverse these negative effects, but the evidence suggests that professionals often fail to expose child abuse. This study aims to generate insight into professionals' experiences with facilitators in handling the challenges of addressing abuse in child interviews. We expect that this knowledge can improve interventions that qualify professionals in the identification, protection and care of abused children. Methods Within the qualitative approach and an Interpretive Description framework, we performed in-depth interviews with nineteen participants from southern Norway, specifically ten social workers from child protective services and nine psychologists from child mental health services. Then, Interpretive Description analysis was performed by using constant comparison, reflexive and critical examinations, and contextualized theoretical interpretations. Results The participants' accounts revealed that various facilitators relative to the stages of the skill development and intrinsic motivation of the practitioner enhance the explorative work of the professional. We identified the following five main themes: (a) alleviating personal choice; (b) collective accountability; (c) sharing vulnerability; (d) finding your own way; and (e) doing it for the right reasons. Conclusions To facilitate explorative work, our findings suggest that competence development should apply goal-directed reflective practice combined with positive feedback on performance. Furthermore, our results indicate that developing personal competence is contingent on supporting individual choice and volition while decreasing demands towards following rules and guidelines. To promote the relatedness and the emotion regulation of professionals, we suggest endorsing shared vulnerability with colleagues and promoting an organizational culture that supports openness and allows professionals to discuss their emotions when addressing difficult and complex issues. It is also advisable to promote autonomy by helping professionals to find meaning in their work that is compatible with their personal values.